2015
DOI: 10.1371/journal.pone.0115435
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Knowledge, Contraception Uptake, and Factors Associated with Unmet Need for Modern Contraception among Adolescent Female Sex Workers in China

Abstract: ObjectiveIn China, policy and social taboo prevent unmarried adolescents from accessing sexual and reproductive health (SRH) services. Research is needed to determine the SRH needs of highly disadvantaged groups, such as adolescent female sex workers (FSWs). This study describes SRH knowledge, contraception use, pregnancy, and factors associated with unmet need for modern contraception among adolescent FSWs in Kunming, China.MethodsA cross-sectional study using a one-stage cluster sampling method was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 32 publications
2
51
2
Order By: Relevance
“…As previously reported,41 inconsistent condom use in the past month with any male partner was reported by 57% of participants; 54% with male intimate partners and 65% with male clients. However, when we included the situation of under illicit drug use in this analysis, the rate of inconsistent condom use was sharply raised for approximately two-thirds of the women, and almost equal with male intimate partners (65%) as with male clients (70%; data not shown).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…As previously reported,41 inconsistent condom use in the past month with any male partner was reported by 57% of participants; 54% with male intimate partners and 65% with male clients. However, when we included the situation of under illicit drug use in this analysis, the rate of inconsistent condom use was sharply raised for approximately two-thirds of the women, and almost equal with male intimate partners (65%) as with male clients (70%; data not shown).…”
Section: Resultssupporting
confidence: 76%
“…Similarly concerning, only 3% of participants had ever used long-acting reversible contraception, and currently using dual methods was reported by only 7% of adolescent FSWs 41. These findings indicate how tackling SGBV and related SRH risks might also help to reduce young women's risk and vulnerability to HIV/STI infection and unwanted pregnancy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We note that while some FSWs know that contraceptives are useful for pregnancy prevention, general knowledge remained poor with some resorting to abortion to terminate an unwanted pregnancy. Elsewhere, a study in China conducted among adolescent FSWs also found general sexual and reproductive health knowledge to be low, and while 98% reported not wanting the pregnancy, less than half (43%) reported consistent condom use with another 28% reporting current use of another contraceptive method [27]. A separate study examining contraceptive use among female entertainment sex workers in Cambodia found several factors to be linked to unwanted pregnancy such as the increase in a number of clients, inconsistent condom use, condom breakage and forced unprotected sex [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, however, should not overshadow the importance of providing early access to contraceptives among young and adolescent FSWs as about one-fourth of 18-24-year-old FSWs in our sample reported a lifetime abortion. Indeed, studies suggest that given the illegal nature of abortion in several settings (e.g., Iran), the profound stigma associated with premarital pregnancy and sexual activity, limited sexual health education for youth and adolescents, and negative attitudes of healthcare providers towards teenage pregnancy, young women and FSWs’ abortion practices are highly under-reported and often carried out within unauthorized and underground health facilities [36–38]. …”
Section: Discussionmentioning
confidence: 99%